Photocatalytic study for fabricated Ag doped and undoped MgFe2O4 nanoparticles. (2017) - Shetty, Krushitha; Prathibha, B.S.; Rangappa, Dinesh; Anantharaju, K.S.; H.P. Nagaswarupa,; Nagabhushana, H.; Prashantha, S.C.
Abstract: In the present study, spinel type Ag doped and undoped MgFe2 O4 nanoparticles (Nps) were synthesized successfully by simple solution combustion synthesis, which shows excellent performance as a photocatalyst for dye decomposition. Structural composition and morphological features were studied by PXRD, FTIR and SEM. Study revealed that the prepared Nps showed simple cubic phase. The Egap of undoped and Ag doped MgFe2 O4 Nps were determined by UV-VIS spectrometer. The photocatalytic process was accomplished in terms of percentage decomposition under visible light irradiation. EIS spectra revealed that Ag doped MgFe2 O4 has the efficient charge separation and best charge transfer rate. The degradation of Metanil Yellow dye is enhanced by Ag doped MgFe2 O4 than undoped MgFe2 O4 Nps this could be attributed to smaller crystalline size, narrow band gap and high light harvesting ability. The photocatalyst synthesized here exhibited reusability with excellent efficiency.